"A journey around the world": Parent narratives of the journey to pediatric resective epilepsy surgery and beyond. (20th April 2015) - Baca, Christine B.; Pieters, Huibrie C.; Iwaki, Tomoko J.; Mathern, Gary W.; Vickrey, Barbara G.
Summary Objective Although shorter time to pediatric resective epilepsy surgery is strongly associated with greater disease severity, other nonclinical diagnostic and sociodemographic factors also play a role. We aimed to examine parent‐reported barriers to timely receipt of pediatric epilepsy surgery. Methods We conducted 37 interviews of parents of children who previously had resective epilepsy surgery at University of California Los Angeles (UCLA; 2006–2011). Interviews were audio‐recorded, transcribed, and systematically coded using thematic analysis by two independent coders, and subsequently checked for agreement. Clinical data, including "time to surgery" (age of epilepsy onset to surgery) were abstracted from medical records. Results The mean time to surgery was 5.3 years (standard deviation [SD] 3.8); surgery types included 32% hemispherectomy, 43% lobar/focal, and 24% multilobar. At surgery, parents were on average 38.4 years (SD 6.6) and children were on average 8.2 years (SD 4.7). The more arduous and longer aspect of the journey to surgery was perceived by parents to be experienced prior to presurgical referral. The time from second antiepileptic drug failure to presurgical referral was ≥1 year in 64% of children. Thematic analysis revealed four themes (with subthemes) along the journey to surgery and beyond: (1) recognition—"something is wrong" (unfamiliarity with epilepsy, identification of medical emergency); (2) searching and finding—"a circuitous journey" (information seeking, finding the right doctors, multiple medications, insurance obstacles, parental stress); (3) surgery is a viable option—"the right spot" (surgery as last resort, surgery as best option, hoping for candidacy); and (4) life now—"we took the steps we needed to" (a new life, giving back). Significance Multipronged interventions targeting parent‐, provider‐, and system‐based barriers should focus on the critical presurgical referral period; such interventions are needed to remediate delays and improve access to subspecialty care for children with medically refractory epilepsy and potentially eligible for surgery.